Effects of surfactant on stability and thermo-physical properties of metal oxide nanofluids. (July 2016) - Khairul, M.A.; Shah, Kalpit; Doroodchi, Elham; Azizian, Reza; Moghtaderi, Behdad
Highlights: Stability of the different nanoparticles is studied. Different SDBS weight concentrations were used in the experiments. Lowest value of the viscosity indicates better stability of nanofluid. Nanofluid's stability is improved with increase in the thermal conductivity. Abstract: Optimal thermo-physical properties of nanofluids provide an opportunity to overcome energy associated difficulties, in addition to providing new alternatives to catch, store and exchange of energy. A significant reduction in energy consumption is possible by improving the performance of a heat exchanger circuit, and may in part alleviate current energy related challenging issues such as global warming, climate change, and the fuel crisis. The objective of this work is to gain an insight into the overall stability of nanofluids with respect to pH, zeta potential, particle size distribution, and its effect on viscosity and thermal conductivity. For the purpose of this study two nanofluids were selected (water based alumina and copper oxide). Various nanoparticles concentrations as well as anionic surfactants (sodium dodecylbenzene sulfonate) were investigated for their stability, viscosity as well as thermal conductivity. The results clearly showed that nanofluid stability has a strong relation with viscosity and thermal conductivity. The stability of the nanofluid was found to be improved with a decrease in viscosity and an increase in thermal conductivity.